A compressive data gathering method based on El Gamal cryptography - Xiaohan YU; Keming DONG; Xia LI; Chao CHEN (Dianxin kexue, 2019)
As a hot researching area,compressive sensing has advantages in signal process,image processing and data gathering and analysis.How to effectively and safely apply compressive sensing technology to collect data in wireless sensor networks is studied.Conventional compressive sensing technology based data collection method does not consider the security issue.Furthermore,every nod in the network must participate in the process of collecting measurements.The El Gamal cryptography and sparse matrices based compressive sensing technology were combined,and the El Gamal based sparse compressive data gathering (ESCDG) method was proposed.Theoretical analysis and numerical experiments show that ESCDG not only decreases the network resource consumption but also be able to defense the internal and external attacks.